Integration of Innovation in Green Human Resources Management: A Systematic Review of Compensation and Reward for Organizational Sustainability: Integration of Innovation in Green Human Resources Management: A Systematic Review of Compensation and Reward for Organizational Sustainability - Agus Kusnawan; Selamet Riyadi; Eryco Muhdaliha; Adi Saputro; Jemmy Jemmy (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
Organizational sustainability has increasingly become a central focus in human resource management (HRM), particularly through the implementation of innovation-based green compensation and reward mechanisms. This study aims to present a systematic review of the role of green compensation and rewards in promoting employees’ pro-environmental behavior and enhancing organizational sustainability through innovative strategies. The review includes 100 articles categorized into five key themes, such as the impact on employee behavior, integration of green HRM practices, green incentives, and the effectiveness of green rewards. The findings indicate that green compensation significantly influences employees’ pro-environmental behavior by enhancing green motivation and organizational commitment (K, 2024). Furthermore, the integration of green HRM practices including green recruitment and innovation-focused training reinforces the alignment between corporate sustainability strategies and employee behavior (K, 2024). Both financial and non-financial incentives designed with a sustainability focus and innovative approaches have also been shown to increase employee engagement in environmental initiatives (Beck-Krala, 2020).  Green reward mechanisms not only raise environmental awareness but also play a crucial role in driving eco-innovation in the workplace (Performance Analysis, 2020). In addition, effective and innovation-based reward systems help organizations achieve higher levels of sustainability by improving employee retention and environmental performance. This study concludes that green compensation and reward are key strategies in green HRM to support sustainability. Further research is needed to explore the implementation of these mechanisms across different cultural and industrial contexts.